Construction of a New Growth References for China Based on Urban Chinese Children: Comparison with the WHO Growth Standards - Zong, Xin-Nan; Li, Hui (PLOS ONE, 2013)
Introduction Growth references for Chinese children should be updated due to the positive secular growth trends and the progress of the smoothing techniques. Human growth differs among the various ethnic groups, so comparison of the China references with the WHO standards helps to understand such differences. Methods The China references, including weight, length/height, head circumference, weight-for-length/height and body mass index (BMI) aged 0–18 years, were constructed based on 69,760 urban infants and preschool children under 7 years and 24,542 urban school children aged 6–20 years derived from two cross-sectional national surveys. The Cole’s LMS method is employed for smoothing the growth curves. Results The merged data sets resulted in a smooth transition at age 6–7 years and continuity of curves from 0 to 18 years. Varying differences were found on the empirical standard deviation (SD) curves in each indicator at nearly all ages between China and WHO. The most noticeable differences occurred in genders, final height and boundary centiles curves. Chinese boys’ weight is strikingly heavier than that of the WHO at age 6–10 years. The height is taller than that of the WHO for boys below 15 years and for girls below 13, but is significantly lower when boys over 15 years and girls over 13. BMI is generally higher than that of the WHO for boys at age 6–16 years but appreciably lower for girls at 3–18 years. Conclusions The differences between China and WHO are mainly caused by the reference populations of different ethnic backgrounds. For practitioners, the choices of the standards/references depend on the population to be assessed and the purpose of the study. The new China references could be applied to facilitate the standardization assessment of growth and nutrition for Chinese children and adolescents in clinical pediatric and public health.